2018
DOI: 10.1007/s12053-018-9707-8
|View full text |Cite
|
Sign up to set email alerts
|

Office building deep energy retrofit: life cycle cost benefit analyses using cash flow analysis and multiple benefits on project level

Abstract: Deep energy retrofit (DER) of the existing building stock is a meaningful strategy to reduce fossil fuel consumption and CO 2 emissions. However, the investment volumes required to undertake DER are enormous. In Europe, cumulative demand for DER is estimated at close to 1000 billion EUR until 2050. Public expenditures and political measures can help to stimulate and guide DER, but substantial private investments are required to achieve significant results. In this paper, we analyze the economic and financial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…They used metaheuristic algorithms such as Tabu search and simulated annealing, and in their research duration of activities has been considered stochastic. Bleyl et al [41] analyzed the implementation of deep energy retrofit (DER) at office buildings and utilized cash flow in order to calculate cost-benefit analysis. They believed that DER can reduce fossil fuel consumption in the world.…”
Section: Introductionmentioning
confidence: 99%
“…They used metaheuristic algorithms such as Tabu search and simulated annealing, and in their research duration of activities has been considered stochastic. Bleyl et al [41] analyzed the implementation of deep energy retrofit (DER) at office buildings and utilized cash flow in order to calculate cost-benefit analysis. They believed that DER can reduce fossil fuel consumption in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Once integrated into the DCFA, the valuation of the environmental externalities from the building energy retrofit provides a cost-benefit analysis (CBA) [53,54]. The socio-economic externalities could be the external costs from the CO 2 emissions, or the external benefit from the reduction of CO 2 emissions.…”
Section: Integrating Externalities Into the Dcfamentioning
confidence: 99%
“…However, sustainable building renovation projects should also consider other project benefits such as increased building values or tenant rates, which is why the benefit assessment is introduced as a so-called economic analysis. Accordingly, Bleyl et al [38] identified multiple project benefits (MPB) for the energy-efficient renovation of office buildings such as increased rents, real estate values, and (employee) productivity as well as savings in maintenance costs and CO 2 . The authors also provide the approaches to the monetization MPB and their monetary values.…”
Section: Cost-benefit Analysismentioning
confidence: 99%
“…However, more sophisticated methodologies are also used such as decision-making (DM) techniques [24][25][26][27][28][29][30], Delphi, investment analysis [31,32], simulation-based sensitivity analyses [33], etc, while some studies deal with residential buildings [34] and some with commercial buildings [35,36]. Some studies [30,[37][38][39][40] have dealt with the economic assessment of sustainable building renovation. In addition, evaluating the degree of sustainability of buildings using green building rating systems is also based on a quantitative multi-criteria assessment approach [10][11][12].…”
Section: Introductionmentioning
confidence: 99%